Analisis Prinsip Desain Logo PAL TV Dalam Perspektif Budaya Digital - Mukhsin Patriansah; Keni Dion (Universitas Bumigora, 2023)
Palembang Television (PALTV) is one of the first television stations in the city of Palembang and South Sumatra. PALTV has been established for approximately 18 years, to be precise on September 9 2005. According to the sources the author reviewed, so far there has been no change to the PALTV logo, starting from its inception in 2005 until now it still uses the same logo. Therefore, PALTV as the first television station in South Sumatra and Palembang City should carry out rebranding so that it can position itself with the needs and developments of the times, especially in aspects of current digital culture. The main problem discussed in this research is how to analyze the PAL TV logo design based on the principles of simple, timeless, proportional and relevant logo design. The results of this research can be seen that visually the PALTV logo does not fully represent digital culture with the development of information and communication technology. Therefore, a rebranding effort is needed to apply the principles of logo design that is simple, timeless, proportional and relevant, so that it has an impact on a visual image that is able to create suggestions and impress the audience, and is relevant to the conditions and culture of the people.